(untitled) (Sebha University Conference Proceedings, 2024)
Recently, there has been growing interest in the use of superplasticizers, which offer significant benefits in improving both fresh and hardened concrete properties. These additives can increase workability, extend setting times (helpful in hot weather or for long-distance transportation), and enhance density, which in turn improves compressive strength. This study investigates the effect of superplasticizers on concrete properties, focusing on the impact of varying the dosage beyond the recommended limits. A concrete mix was designed using the american method, incorporating two types of superplasticizers (sika® viscoconcrete® tempo-12) and (sikament-ff) at different percentages (0.5%, 1%, 2%, 4%) of the cement weight. The results were compared to a reference concrete mix without any additives. The findings show that increasing the proportion of superplasticizers within recommended limits led to higher compressive strength compared to the reference mix. Among the superplasticizers tested, (sika® viscoconcrete® tempo-12) yielded a higher compressive strength than (sikament-ff), although strength declined when the additive percentages exceeded the optimal range. In terms of workability, the slump test results indicated that the mix containing (sikament-ff) exhibited greater workability than the mix with (sika® viscoconcrete® tempo-12). Moreover, the absorption test revealed that (sikament-ff) reduced the absorption rate, while (sika® viscoconcrete® tempo-12) showed a slight increase in absorption as the dosage increased. In both cases, superplasticizers improved the concrete properties compared to the reference mix.